Treating Yourself in a Fairway: Examining the Contribution of Self-Compassion and Well-Being on Performance in a Putting Task - Melanie R. Burgess; Diane E. Mack; Philip M. Wilson; Leah J. Ferguson (Sports)
Researchers have advocated for greater insight regarding the contributions of psychological resources to sports performance. The purpose of this study was to examine the contributions of self-compassion and well-being to sports performance using a golf putting task. Male golfers (N = 87, Mage = 54.94; SDage = 15.37 years) completed the Self-Compassion Scale—Athlete Version and the Warwick Edinburgh Mental Well-Being Scale immediately prior to the golf putting task which consisted of 15 consecutive putts from 7 feet on an outdoor practice green. Performance was assessed immediately following the putting task. Simple linear regression analyses showed that self-compassion did not predict ‘perceived’ (β = −0.20, p = 0.06; ƒ2 = 0.04) or ‘actual’ (β = −0.17, p = 0.11; ƒ2 = 0.03) performance. Similarly, well-being did not predict ‘perceived’ (β = −0.16, p = 0.15; ƒ2 = 0.03) or ‘actual’ performance (β = −0.01, p = 0.91; ƒ2 = 0.00). Overall, the conclusions from this study offer converging evidence that self-compassion and well-being may not impact putting performance in adult male golfers. Greater insight into whether, and if so under what conditions, self-compassion and well-being matter to sports performance warrants additional scrutiny.